Enhanced Ethanol Production From Carbon Monoxide by Enriched Clostridium Bacteria - He, Yaxue; Lens, Piet N. L.; Veiga, María C.; Kennes, Christian (Frontiers in Microbiology, 2021)
CO metabolizing Clostridium spp. were enriched from the biomass of a butanol-producing reactor. After six successive biomass transfers, ethanol production reached as much as 11.8 g/L with minor accumulation of acetic acid, under intermittent gas feeding conditions and over a wide pH range of 6.45 to 4.95. The molar ratio of ethanol to acetic acid exceeded 1.7 after the lag phase of 11 days and reached its highest value of 8.6 during the fermentation process after 25 days. Although butanol production was not significantly enhanced in the enrichment, the biomass was able to convert exogenous butyric acid (3.2 g/L) into butanol with nearly 100% conversion efficiency using CO as reducing power. This suggested that inhibition of butanol production from CO was caused by the lack of natural butyric acid production, expectedly induced by unsuitable pH values due to initial acidification resulting from the acetic acid production. The enriched Clostridium population also converted glucose to formic, acetic, propionic, and butyric acids in batch tests with daily pH adjustment to pH 6.0. The Clostridium genus was enriched with its relative abundance significantly increasing from 7% in the inoculum to 94% after five successive enrichment steps. Unidentified Clostridium species showed a very high relative abundance, reaching 73% of the Clostridium genus in the enriched sludge (6th transfer).